2015
DOI: 10.1002/bse.1884
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Environmental Management Systems: the Role of Motivations and Firms’ Characteristics

Abstract: This article analyzes the influence of the sources of motivation that lead companies to adopt environmental management systems (EMSs) on the outcomes of these systems. A set of hypotheses derived from an extensive review of the literature is analyzed using cluster analysis – in order to identify groups of companies – as well as correlation and regression analyses, with data obtained from a survey of 361 Spanish organizations that have environmental certification. The results reveal that, for the groups identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 61 publications
2
87
0
4
Order By: Relevance
“…For example, Guoyou et al (2012) concluded that the internal motivation was the main driving force of internalizing ISO 14001. Similarly, in a recent survey on EMAS registered organizations, Heras-Saizarbitoria et al (2015a) evidenced that the internal drivers have a significantly higher influence on the perceived benefits of the adoption, irrespective of the size, the sector of activity and the environmental pressures of the company. Conversely, external motivations to adopt EMSs, such as market demand, are not necessarily in line with the internal needs related to environmental management practices (Christmann and Taylor, 2006;Heras-Saizarbitoria et al, 2011;Boiral, 2007Boiral, , 2011.…”
Section: Motivation For Environmental Certificationmentioning
confidence: 85%
“…For example, Guoyou et al (2012) concluded that the internal motivation was the main driving force of internalizing ISO 14001. Similarly, in a recent survey on EMAS registered organizations, Heras-Saizarbitoria et al (2015a) evidenced that the internal drivers have a significantly higher influence on the perceived benefits of the adoption, irrespective of the size, the sector of activity and the environmental pressures of the company. Conversely, external motivations to adopt EMSs, such as market demand, are not necessarily in line with the internal needs related to environmental management practices (Christmann and Taylor, 2006;Heras-Saizarbitoria et al, 2011;Boiral, 2007Boiral, , 2011.…”
Section: Motivation For Environmental Certificationmentioning
confidence: 85%
“…Many empirical works have analyzed the main drivers and the drivers related to the outcomes of environmental certifiable meta‐standards (Boiral et al, ; Heras‐Saizarbitoria & Boiral, ; Sartor et al, ), considering the connection between the level of internalization and completeness of adoption of the standards and the motivations (Heras‐Saizarbitoria, Arana, & Boiral, ; Heras‐Saizarbitoria et al, ; Lannelongue, Gonzalez‐Benito, & Gonzalez‐Benito, ). These works have evidenced that the adoption of environmental meta‐standards such as ISO 14001 and EMAS can be driven by various internal and external motivations (Fryxell, Lo, & Chung, ; Gavronski, Paiva, Teixeira, & de Andrade, ; González‐Benito & González‐Benito, ; Heras‐Saizarbitoria et al, , ). Among the external factors of motivations, as pointed out by Heras‐Saizarbitoria and Boiral () in their review, together with company image drivers and the motivation to send out a message to potential consumers by stressing the company's environmental concern (King et al, ), the empirical literature emphasizes the influence of customer pressure and the pressure by the public administration.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Moreover, according to HerasSaizarbitoria et al (2015), EMAS is more internally focused. Firms aim to obtain positive outcomes from improved internal processes [19]. Generally, a firm's size influences the internalization of proactive environmental practices.…”
Section: Barriers and Challenges That Organizations Face In The Implementioning
confidence: 99%